DEVELOPMENT FOR AIR NAVIGATION SERVICES - Алєксєєв, О.; Креденцар, С.; Скоробогата, Х. (Proceedings of National Aviation University, 2012)
To solve the problem of air navigation services need to develop methods for integrating air navigation system of Ukraine according to European norms. This can be done by improving the development of information systems of air transport for various departments. Specific character of an air transport constantly makes us to improve all its systems that provide the normal functioning of the whole transport sector. Improving the air transport system is inevitably linked with the development of information flight service tools for various departments. The set of system nodes and links between them, the distribution of tasks assigned to technical facilities according levels and nodes of the system and the choice of technical tools for effective solution are determined during structure developing. Thus, it is necessary to identify the problems of air navigation services and to create solutions based on the world experience